Inventory, Warehousing and Transportation Management Impacts Towards Logistics Performance in Supply Chain Management - Mohd fathi Mohamad; Zulkifli M Udin; Kamal imran Sharif (International Journal of Supply Chain Management, 2018)
Abstract The purpose of this article is to proposed a framework that related to the factors that impacts the logistics performance due to lack of equal agreement on the factors that affecting logistics performance. Factors that been proposed in this article includes inventory management, warehouse management and transportation management. It will also be discussing others general factors that affecting the logistics performance. A comprehensive discussion on all three variables been done in order to provides greater insight on the factors that affecting the logistics performance. These comprehensive reviews include the management of inventory, warehousing and transportation and provides greater definition on the variables terminology that are related. Therefore, a framework has been proposed for further study